Uncertainty in Crack width Estimates According to Fib Model Code 2010 - Mlčoch Jan; Marková Jana; Sýkora Miroslav (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2017)
The contribution is focused on quantifying model uncertainty of crack width estimates for reinforced concrete beams. Predictions obtained by the model provided by the fib Model Code 2010 are compared with results of tests of beams having different longitudinal and shear reinforcement ratios and concrete cover. Trends of model uncertainty with basic variables are investigated.